New forms of strong compactness in terms of ideals (2016)
The aim of this paper is to introduce and study new types of strong compactness, modulo an ideal, called ρI-compactness and σI-compactness. Several of their properties are presented and some effects of various kinds of functions on them are studied. We compare this new spaces with other known types of strong compactness modulo an ideal.